(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2016)
Substantiated changes in the structure of the internal control system, given its participation in the processes of economic security of enterprise. Identified possible limitations of internal control system related to the expression of the relevant types of risk, expanded requirements for professionals of internal control for their work with risk of activity. Range of objects of internal control system defined as a component of economic security of enterprise: 1) at the enterprise level (display control of the system and therefore covers all of general nature risks, which may affect on the activity of the enterprise as a whole); 2) at the level of departments and services (displays control of subsystems and associated with the assessment of the risks that occur in the structural units of the enterprise); 3) the level of individual transactions (displays control of elements and implemented during, before and after the business operations associated with the expression of specific types of economic risk, technical, technological risks, social and other risks).